The Effect of Moderate-Intensity Continuous Training with Game Two Touches on the Passing and Receiving Ability of U-15 Soccer Players - Listyawan, Brillian Jacka; Kusuma, I Dewa Made Aryananda Wijaya; Syafii, Imam; Prianto, David Agus (Universitas Negeri Surabaya, 2024)
Purpose: This study aimed to determine the influence of Moderate-Intensity Continuous Training (MICT) combined with a two-touch game on the passing and receiving abilities of Persebra U15 soccer players. MICT was conducted at an intensity of 40-60% of maximum heart rate for 45 minutes per session, three times a week, for six weeks. Players performed continuous passing and receiving drills within a small-sided game that allowed a maximum of two touches per player. Materials and Methods: This study used a one-group pretest-posttest experimental design with 10 Persebra U15 players. Passing and receiving skills were assessed using standard tests before and after the 6-week intervention. Result: Paired t-test analysis showed a significant improvement in mean passing and receiving scores from pre- to post-test (mean difference 1.0, p=0.015). Conclusion: The findings suggest that MICT combined with a two-touch, small-sided game can effectively enhance the essential technical skills of young soccer players. Improving passing and receiving abilities through structured training leads to the positive development of individual playing skills and team performance